EMPOWERMENT SCHOOL DROPOUTS THROUGH FUN LEARNING TO PREVENT EARLY MARRIAGE IN CEPOKO VILLAGE, SUMBER DISTRICT, PROBOLINGGO - Anggraini , Ade Eka; Mugi Praseptiawan; Jati Fatmawiyati; Khusnul Khotimah; Zativalen, Oriza (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
Every citizen has the right to receive education and the state is responsible for financing it. This is needed to raise awareness in the community that education is very important. With education we can prevent early marriage. The purpose of this community service activity is to provide an understanding of the importance of education as an effort to strengthen the community's understanding of the consequences of early marriage. The target of this activity is to provide socialization to the community in Sumber Village, Sumber District, Probolinggo Regency. Based on this activity, the results obtained were that raising public awareness to increase knowledge so that children at the age that should be following formal education do not stop due to financial constraints, so that they are not forced to only complete basic education and undergo marriage at an inappropriate age. and Increasing public awareness of the importance of attention and concern for children's educatio